Characterization and anti-inflammatory activity determination of Sindora supa Merr. (Supa) - Mariano, Jose Emmanuel C.; Lazara, Carla Beatriz H.​; Masula, Jecelle D.​ (2017)
Sindora supa Merr. (Fam. Fabaceae), commonly known as supa, is an endemic species found at low to medium altitudes in Luzon (Fernando et al., 2004). Its wood is prized for its durability and pleasant aroma,while it soil is traditionally used as external medicine for eczema and other skin diseases (Quisumbing, 1951).No investigation, however, has been made into the properties of its other parts, such as the leaves, and altogether only limited research exists on the plant. S. supa was characterized in the study through phytochemical screening and DNA barcoding. The crude ethanolic leaf extract was also evaluated for anti-inflammatory activity with the modified HET?CAM (hen?s egg test-chorioallantoic membrane) method to establish its potential for herbal product development. Phytochemical screening of the crude ethanolic leaf extract indicated the presence of phenols, flavonoids, saponins, andcardiac glycosides. DNA sequences of the matK region were obtained and showed, at the highest, a max identical value of 99% (E-value = O) with other sequences of S. supa and related species. Results ofthe modified HET-CAM assay showed moderate inflammation inhibition at concentrations of 100 and 10mcg.